The Living Wage Debate in the Kenyan Cut-Flower Industry - Kuiper, Gerda (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
Over the past three decades, the Kenyan cut-flower industry has come under intense scrutiny for its environmental impacts and poor labor conditions, including low wages. A multitude of certification schemes have been introduced to address this criticism, each with its own regulations and standards. However, these certifications have had little impact on industry wages. Even though the most well-known standard, Fairtrade, explicitly targets living wages, wage levels remain well below living wage calculations for Kenya’s flower-producing hubs. This article explores this discrepancy. First, I discuss local experiences with wage levels in the major flower-growing hub at Lake Naivasha. This discussion indicates that local evaluations of wage levels in the flower industry are more differentiated than global discussions on the living wage suggest. Secondly, I argue that certifications, including their measures to support living wages have a depoliticizing effect and side-line local mechanisms for setting wage levels. Consequently, living wages in the Kenyan flower industry are still a long way from materializing.